Bases institucionais e interfaces na seguridade social brasileira: Uma análise macrossetorial - Luciana Jaccoud (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– This article provides an analysis of the propriety and opportunity of a macrosectoral analysis of Brazilian social security, in order to favor the understanding of the performance and challenges that cross each of its sectoral policies and contribute to the reflection on the common logic that embraces health, social insurance and assistance policies, their interfaces and interdependencies. At first, it rescues the sectoralization process that progressively marked this field of public policies. Then, it recovers the institutional design that welcomed social security in its tripod, and empirically explores some aspects of the interdependence between the sectorial fields of social security. The possibility of implementing articulation instruments in favor of greater coordination between policies in this field is also discussed.
Keywords: I31; 330; social security; inequality; policy integration; intersectionality